1989
DOI: 10.1128/aem.55.3.741-746.1989
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Biological Control of Agrobacterium tumefaciens Strains Sensitive and Resistant to Agrocin 84 by Different Agrobacterium radiobacter Strains on Stone Fruit Trees

Abstract: The effectiveness of Agrobacterium radiobacter K84, 0341, and a K84 non-agrocin-producing mutant (K84 Agr-) in biological control of crown gall on rootstocks of stone fruit trees was determined in three experiments. In experiment 1, K84 and 0341 controlled crown gall on plum plants in soil inoculated with two strains of Agrobacterium tumefaciens resistant to agrocin 84. In experiment 2, K84 controlled crown gall on peach plants in soils inoculated with strains of A. tumefaciens sensitive or resistant to agroci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
6

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 21 publications
0
14
0
6
Order By: Relevance
“…Genes encoding agrocin 84 biosynthesis are expressed in bacteria colonizing plant roots, and their expression is regulated by root exudate and by nopaline (44). L6pez et al (21) have demonstrated that other mechanisms must be implicated in this biocontrol because strain K84 cured of pAgK84 was as effective as its agrocinogenic parent in controlling A. tumefaciens strains resistant to agrocin 84. They suggested that mechanisms such as root colonization, blockage, and competition for infection sites could be involved in biological control.…”
mentioning
confidence: 99%
“…Genes encoding agrocin 84 biosynthesis are expressed in bacteria colonizing plant roots, and their expression is regulated by root exudate and by nopaline (44). L6pez et al (21) have demonstrated that other mechanisms must be implicated in this biocontrol because strain K84 cured of pAgK84 was as effective as its agrocinogenic parent in controlling A. tumefaciens strains resistant to agrocin 84. They suggested that mechanisms such as root colonization, blockage, and competition for infection sites could be involved in biological control.…”
mentioning
confidence: 99%
“…This strain does not produce agrocin 84 or 434, and the results suggest that chromosomally determined characteristics alone do not play an important role in biocontrol with this pathogen and test system. A number of workers have suggested previously that blockage of or competition for infection sites may explain the biological control of strains resistant to agrocin 84 (8,11,22,38). Other possible mechanisms which may play a role in control include substrate competition in soil (22) and a superior root colonizing ability of biocontrol strains a Superscript numbers indicate strains which are significantly different (P Ͻ 0.05); i.e., a strain with superscript 1 is significantly different from a strain with superscript 2, and a strain with superscript 1,2 is not significantly different (P Ͻ 0.05) from strains with superscript 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
“…Both strains K84 and K1026 produce an antibiotic-like product, agrocin 84, which specifically inhibits the activity of many Agrobacterium pathogens (13,20,21). A number of researchers have suggested that other mechanisms of control may also be involved, including competition for nutrients or for attachment sites and production of additional inhibitory agents (8,9,22,39). Early evidence for the involvement of factors other than agrocin K84 was obtained when control was observed with pathogenic strains insensitive to agrocin 84 (8,22,25,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi, le pourcentage de souches sensibles à K 84 est plus élevé chez le biovar 2 (92%) que le biovar 1 (71%), alors qu'il reste élevé (92 -97%) pour la K 1026 pour les deux biovars. Ces résultats sont différents de ceux obtenus par Schroth & Moller (1976), López et al (1989) et Bouzzar et al (1991 avec la K 84 et nous estimons que l'utilisation du milieu MG dans notre travail a augmenté la qualité de l'antagonisme in vitro par rapport au milieu de Stonier (1960) utilisé par ces auteurs. La K 1026 est d'utilisation récente, datant des années 1998.…”
Section: Influence Du Biovarunclassified